2021
DOI: 10.15850/amj.v8n2.2281
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of In-Hospital Mortality among Patients with Acute Coronary Syndrome: A Single-Center Study in West Java, Indonesia

Abstract: Background: Acute Coronary Syndrome (ACS) is a severe manifestation of coronary artery disease, classified into unstable angina (UA), non-ST-segment elevation myocardial infarction (NSTEMI), and ST-segment elevation myocardial infarction (STEMI). In-hospital mortality in patients with ACS remains high despite the advancement of therapy. This study aimed to evaluate the characteristics of in-hospital mortality among ACS patients in West Java, Indonesia.Methods: This descriptive cross-sectional study analyzed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…The incidence of acute coronary syndrome in patients with hypertension is five times greater than in normotensive patients. Previous studies found that hypertension is a major risk factor for acute coronary syndrome [18,17]. However, this result is not in line with a study by Pramudyo, which found that hypertension is not related to the mortality risk in ACS patients [16].…”
Section: Acute Coronary Syndrome Characteristicscontrasting
confidence: 60%
See 1 more Smart Citation
“…The incidence of acute coronary syndrome in patients with hypertension is five times greater than in normotensive patients. Previous studies found that hypertension is a major risk factor for acute coronary syndrome [18,17]. However, this result is not in line with a study by Pramudyo, which found that hypertension is not related to the mortality risk in ACS patients [16].…”
Section: Acute Coronary Syndrome Characteristicscontrasting
confidence: 60%
“…The prevalence of myocardial infarction is higher in individuals over the age of 60 compared to individuals under the age of 60 [11]. A previous study on characteristics of in-hospital mortality in ACS patients found an increased risk of comorbidities among the elderly population [17].…”
Section: Acute Coronary Syndrome Characteristicsmentioning
confidence: 88%